The moderating role of reputation risk in the relationship between media exposure, corporate social responsibility compliance, and customer perception - Khan, Hadi Hassan; Vatcharapol Sukhotu; Vimolwan Yukongdi; Shah, Faiz H.; Lu, Chung-Cheng; BUITEMS Quetta, Pakistan; Asian Institute of Technology Fellowship (Pathumthani : Asian Institute of Technology, 2020)
This study attempted to empirically test the moderation by reputation risk on customer perception through media exposure and CSR compliance in the Sialkot Sports Industry, Pakistan. The study proposed that CSR compliance and media exposure positively affected the customer perception of the products of the Sialkot Sports Industry, whereas reputation risk negatively moderated these relationships. Using a self-administered questionnaire developed for each variable in the study, data were collected from 451 customers of the Sialkot Sports Manufacturing industry, Pakistan by using convenient sampling technique. The scales were tested for their validity and reliability through exploratory and confirmatory factor analyses and Cronbach{u2019}s alpha. The age and gender and experience of the customer were set as the control variables in the testing of moderation. The hierarchical multiple regression analysis (HMRA) and multigroup analysis (MGA) was used to test the main set of hypotheses for the total sample and within subgroups (international and domestic customers). All the assumptions of BLUE estimates were tested and found statistically established. It was found that media exposure and CSR compliance had a significant impact on customer perception. The results also revealed a statistically significant negative impact of reputation risk on customer perception. Furthermore, reputation risk moderated the effects of media exposure and CSR compliance on customer perception. The study can suggest that media exposure is an important element in building customer perception whereas, CSR compliance is not of primary importance in this regard though it is a requirement as per the international standards for better business in the Sialkot Sports manufacturing industry. The study adds empirical evidence to the existing literature in its finding of the CSR compliance, media exposure and reputation risk for customer perception are not different at the group level of different customers in the case of the sports manufacturing industry. The study contributes and testifies the Kano{u2019}s model of customer satisfaction/perception. Lastly, the study gives one of the practical insights into the many aspects to focus on the Sialkot Sports Industry to improve customer{u2019}s perception.
A Dissertation Submitted in Partial Fulfillment of the Requirements for the Degree of Doctor of Philosophy in Management, School of Management
Thesis (Ph.D.) - Asian Institute of Technology, 2020
Keywords: Social responsibility of business; Customer relations